(3cJGH aj NhGU GdGMLGQs
(3ChdgG (B:s
(3GdMeO ddg GdYRjR GdZaGQ GdhGMO GdgbGQ agPG cJGH hVYJg aj NhGU GdGMLGQ jMJGLg cd Pj dH ef Phj GdGbOGQ djYQa eG ajgG ef GdfaY heG ajgG ef GdGSQGQ s
(3BNQgG (B:s
(3hgh MLQ hLO aj QCSgG aj Mce HfObI UZjQI hLedI jfaY GdedOhZ JYdjbkG hjbWY fRa GdOe hYSQ GdHhd s
(3Vef eLehY , JQJjHgG (B: 2s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs